2017
DOI: 10.9790/3013-0703017291
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological and therapeutic importance of Eucalyptus species grown in Iraq

Abstract: Abstract:-Eucalyptus species grown in Iraq were included Eucalyptus bicolor (Syn: Eucalyptus largiflorens), Eucalyptus griffithsii, Eucalyptus camaldulensis (Syn: Eucalyptus rostrata) Eucalyptus incrassate, Eucalyptus torquata and Eucalyptus microtheca (Syn: Eucalyptus coolabahs). Eucalypts contained volatile oils which occurred in many parts of the plant, depending on the species, but in the leaves that oils were most plentiful. The main constituent of the volatile oil derived from fresh leaves of Eucalyptus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 69 publications
4
87
0
6
Order By: Relevance
“…These results are consistent with previous scientific literature except that saponins were not detected [4].…”
Section: Discussion:-supporting
confidence: 83%
See 2 more Smart Citations
“…These results are consistent with previous scientific literature except that saponins were not detected [4].…”
Section: Discussion:-supporting
confidence: 83%
“…Cordia myxa fruit is regarded as a good source for fibers, proteins and carbohydrates, and some studies suggest promoting the fruit as a carbohydrate and protein supplement for cereal-based diets in poor rural communities [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of the mode of action revealed that the hypotensive effect was more likely due to activation of parasympathetic ganglia and dilatation of peripheral blood vessels, whereas the respiratory stimulant effect may partly be due to activation of chemoreceptors in the aortic arch and carotid body. In addition, a sub-effective dose of the ripe fruit mucilage specifically antagonized nicotineinduced hypotensive effect on rabbit and nicotine ganglionic stimulant effect on the isolated guinea pig ileum [87][88].…”
Section: Cordia Myxamentioning
confidence: 99%
“…In contrast, Cordia myxa extractinduced relaxation was potentiated by Nw-nitroLarginine (L-NOARG) treatment. Accordingly, the Cordia myxa extract -induced relaxation may be due to nitric oxide from aupplied exogenously administered Larginine as well as endogenous nitric oxide donors such as amino acid and arginine derivatives [65][66].…”
Section: +mentioning
confidence: 99%